TUG1 suppresses neural repair subsequent to cerebral hemorrhage via the miR-381-3p/BDNF axis - Li, Fei; Zhang, Xin; Jiang, Hong; Zhang, Hui; Chen, Qian (Folia Neuropathologica, 2026)
Intracerebral hemorrhage (ICH) has a high rate of death and disability. LncRNA-TUG1 is essential for the pathological changes secondary to ICH. The purpose of this work was to investigate the possible mechanism by which TUG1 inhibits neural repair subsequent to ICH through adjusting miR-381-3p/brain-derived neurotrophic factor (BDNF). After the ICH model was created, miR-381-3p agomir and pcDNA-TUG1 were injected. The neural function of rats was estimated using the modified neurological severity score. To quantify the expression of genes and proteins, western blotting, immunohistochemistry, and qRT-PCR were used. To confirm the interaction between TUG1 and miR-381-3p and between miR-381-3p and BDNF mRNA, a luciferase reporter assay was employed. In rats treated with miR-381-3p agomir, a trend of improvement in neurological dysfunction was observed, while the pcDNA-TUG1-treated ones showed deterioration. Furthermore, miR-381-3p agomir increased, while pcDNA-TUG1 reduced the expression level of BDNF in ICH rats. TUG1 and BDNF mRNA were validated to attach directly to miR-381-3p. Overexpressing TUG1 inhibited the level of BDNF by sponging miR-381-3p and antagonized its protective effect on neural repair in ICH rats. Our study suggests that TUG1 can sponge miR-381-3p to downregulate BDNF expression and inhibit neural repair following ICH, demonstrating a potential signaling pathway that is conducive to a better understanding of the pathological mechanisms of ICH.